The error is on line 4, which is the second to last line.
The person factored out 10 on the left hand side, when they should have factored out 11 instead.
Also, they factored out 11 on the right hand side when it should have been 10.
This is what line 4 should look like
11(x+y-z) = 10(x+y-z)
which leads to
11 = 10
when you divide both sides by (x+y-z)
But keep in mind that x+y = z is the first line. If you subtract z from both sides, you get x+y-z = 0. So going from line 4 to line 5, they divided by x+y-z = 0 which is not allowed. If division by zero was allowed, then we could come up with all sorts of weird contradictions like this proof is trying to do.